The state of the art of sound therapy for subjective tinnitus in adults - Haiyan Wang; Dongmei Tang; Yongzhen Wu; Li Zhou; Shan Sun (SAGE Publishing, 2020)
Background: Sound therapy is a clinically common method of tinnitus management. Various forms of sound therapy have been developed, but there are controversies regarding the selection criteria and the efficacy of different forms of sound therapy in the clinic. Our goal was to review the types and forms of sound therapy and our understanding of how the different characteristics of tinnitus patients influence their curative effects so as to provide a reference for personalized choice of tinnitus sound therapy. Method: Using an established methodological framework, a search of six databases including PubMed identified 43 records that met our inclusion criteria. The search strategy used the following key words: tinnitus AND (acoustic OR sound OR music) AND (treatment OR therapy OR management OR intervention OR measure). Results: There are various forms of sound therapy, and most of them show positive therapeutic effects. The effect of customized sound therapy is generally better than that of non-customized sound therapy, and patients with more severe initial tinnitus respond better to sound therapy. Conclusion: Sound therapy can effectively suppress tinnitus, at least in some patients. However, there is a lack of randomized controlled trials to identify effective management strategies. Further studies are needed to identify the most effective form of sound therapy for individualized therapy, and large, multicenter, long-term follow-up studies are still needed in order to develop more effective and targeted sound-therapy protocols. In addition, it is necessary to analyze the characteristics of individual tinnitus patients and to unify the assessment criteria of tinnitus.